Perceived barriers by university students in relation the leisure-time physical activity. http://dx.doi.org/10.5007/1980-0037.2013v15n2p164 - Thiago Ferreira de Sousa; Silvio Aparecido Fonseca; Aline Rodrigues Barbosa (Universidade Federal de Santa Catarina, 2013)
To estimate the prevalence and socio-demographic indicators and program affiliation associated with the perceived barriers for physical activity practice; and, to analyze the association between the perceived barriers with leisure-time physical inactivity in university students. A cross-sectional study was carried out with a representative sample (n=1084) of university students (N=5,461) of a public university from the state of Bahia, Brazil. The information were obtained for Isaq-A questionnaire and the perceived barriers in relation to the leisure-time physical activity were categorized as situational, personal and arising from resources and analyzed in relation the socio-demographic indicators (gender, age, partner status and hours in occupational activities), program affiliation (period of study and year of entrance at the university) and leisure-time physical inactivity. The association was estimated by Prevalence Ratio (Poisson Regression Analysis). The significance value was of 5%. The most prevalent barrier was situational (56.7%), and higher with more years of exposure academic (p=0.02). Higher prevalence of leisure time physical inactivity was observed in university students that perceived the barriers of resources (PR=2.59; 95%CI=1.17-5.71). The barriers situational were more mentioned, especially, in the final years of the course, however, the barriers of resources represented association with leisure-time physical inactivity.